2003
DOI: 10.1016/s0960-9822(03)00445-7
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration: Maintaining the Perception of Synchrony

Abstract: We are rarely aware of differences in the arrival time of inputs to each of our senses. New research suggests that this is explained by a 'moveable window' for multisensory integration and by a 'temporal ventriloquism' effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
242
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(252 citation statements)
references
References 15 publications
10
242
0
Order By: Relevance
“…More recently, it has been demonstrated that a sound presented in close temporal proximity to a visual stimulus may be perceived as occurring simultaneously with the visual stimulus. Known as the ''temporal ventriloquism effect,'' this phenomenon can correct for asynchronous auditory and visual inputs by binding visual stimuli into temporal alignment with the appropriate auditory events (19)(20)(21)(22). This phenomenon has not been investigated systematically in freely behaving animals in the field.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been demonstrated that a sound presented in close temporal proximity to a visual stimulus may be perceived as occurring simultaneously with the visual stimulus. Known as the ''temporal ventriloquism effect,'' this phenomenon can correct for asynchronous auditory and visual inputs by binding visual stimuli into temporal alignment with the appropriate auditory events (19)(20)(21)(22). This phenomenon has not been investigated systematically in freely behaving animals in the field.…”
Section: Discussionmentioning
confidence: 99%
“…For temporal judgments, however, such as that studied by Shams et al [10] and others (e.g. [12]), the situation is reversed and audition, being the more appropriate modality, usually dominates over vision. However, the terminology used, 'modality precision' and 'modality appropriateness', is misleading because it is not the modality itself or the stimulus that dominates.…”
Section: Box 1 What Is a Cue? Combination Versus Integrationmentioning
confidence: 95%
“…These signals have different processing latencies due to dissimilarity in physical and neural transmission (Fain, 2003;King, 2005;King & Palmer, 1985;Spence & Squire, 2003). The human brain overcomes these differences by allowing the auditory and visual information to be processed as pertaining to the same event even when the signals are physically asynchronous (Dixon & Spitz, 1980).…”
Section: Visual and Visuomotor Experience In Action Observationmentioning
confidence: 99%